2015
DOI: 10.1080/14786419.2015.1028060
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity and phenolic composition of leaves from 10 Bene (Pistacia atlanticasubsp.kurdica) genotypes

Abstract: Leaves of 10 Bene genotypes were collected from six provinces (West Azerbaijan, Kurdistan, Kermanshah, Ilam, Hamedan and Lorestan) in Iran. This study was carried out to better characterise the total phenolic and flavonoid contents, antioxidant capacity and phenolic composition, as well as to evaluate the correlation between content of phenolic compounds and antioxidant activity in 10 genotypes of Bene. The antioxidant activity of leaf extracts was measured using different assays: ferric reducing antioxidant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…A positive relation between phenolic compounds as potent hydrogen donors and DPPH radical scavenging activity has been reported by Chirinos et al (2010), Myoda et al (2010), and Hatamnia et al (2014Hatamnia et al ( , 2015. However, the present results indicated that hull extract with high phenolic content may play a major role in scavenging of free radicals.…”
Section: Dpph (22-diphenyl-1-picrylhydrazyl) Radical Scavenging Assaycontrasting
confidence: 77%
See 3 more Smart Citations
“…A positive relation between phenolic compounds as potent hydrogen donors and DPPH radical scavenging activity has been reported by Chirinos et al (2010), Myoda et al (2010), and Hatamnia et al (2014Hatamnia et al ( , 2015. However, the present results indicated that hull extract with high phenolic content may play a major role in scavenging of free radicals.…”
Section: Dpph (22-diphenyl-1-picrylhydrazyl) Radical Scavenging Assaycontrasting
confidence: 77%
“…A high positive correlation between phenolic compounds and FRAP assay has been reported by Alañón et al (2011). Some authors have suggested the fact that the FRAP assay was one of the major trials to confirm antioxidant activity (Gourine et al 2010;Farhoosh et al 2011;Hatamnia et al 2014Hatamnia et al , 2015.…”
Section: Frap (Ferric Reducing Ability Of Plasma) Assaymentioning
confidence: 80%
See 2 more Smart Citations
“…22,23 For the total flavonoids content, lower values have been reported for P. atlantica from the south-west of Morocco and Iran. 22,24 This could be explained by different factors as the genetic variability of the plant and the effect of the climat which is more tempered in the south of Morocco thanks to the oceanic influence. Table 3 shows the antioxidant activity evaluated by the three techniques.…”
Section: Discussionmentioning
confidence: 99%